Keefektifan Permainan "Two Truths and A Lie" Dalam Meningkatkan Self Awareness - Ramadhani, Mahmud Shofi; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Dharmas Education Journal (DE_Journal), 2025)
The purpose of this study was to determine the effectiveness of the game “two truths and a lie” in increasing self-awareness. Self-awareness is a person's ability to understand oneself deeply, both in terms of emotions, thoughts, and actions. The Two Truths and a Lie game is a social game that is often used for introductions or building intimacy in groups. In this game, each participant takes turns delivering three statements about themselves. Two of the statements must be true (truth) and one statement must be false (lie). The other participants have to guess which statement is a lie. By using “Two Truths and a Lie,” students can get to know each other better, which is an important first step in the guidance and counseling process. This study uses an experimental research method, which aims to determine the effectiveness of the Two Truths and a Lie game treatment on students' Self-awareness. In this study, the design used is One Group Pretest-Posttest Design, where the results of children's abilities are measured before and after being given treatment. The results showed that there was a significant increase in students' Self-awareness after being given the Two Truths and a Lie game. Statistical testing using the Wilcoxon test indicated an increase in students' Self-awareness. On positive ranks in the test, 12 students showed an increase in Self-awareness from pretest to posttest. In addition, there was no decrease in students' Self-awareness.